2014
DOI: 10.1136/gutjnl-2014-306947
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow Th17 TNFα cells induce osteoclast differentiation, and link bone destruction to IBD

Abstract: Our results highlight the osteoclastogenic function of the Th17 TNF-α(+) cells that contribute to bone loss in vivo in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
100
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 32 publications
3
100
1
7
Order By: Relevance
“…A recent study show that the osteoclastogenic function of the Th17 TNFa ? cells that contribute to bone loss in IBD animal model [26]. Contrary to our findings, a number of studies have reported beneficial effect for IFX on bone turnover markers in patients with CD in the short term [27][28][29][30][31].…”
Section: Discussioncontrasting
confidence: 66%
“…A recent study show that the osteoclastogenic function of the Th17 TNFa ? cells that contribute to bone loss in IBD animal model [26]. Contrary to our findings, a number of studies have reported beneficial effect for IFX on bone turnover markers in patients with CD in the short term [27][28][29][30][31].…”
Section: Discussioncontrasting
confidence: 66%
“…Alternatively, microbiota may affect bone resorption indirectly, via modulation of the immune system. Proosteoclastogenic TNF-α-and IL-17-producing CD4 T cells are associated with inflammatory-bowel-disease-induced bone loss (61), and it has been reported that conventionally raised mice have more bone marrow CD4 T cells and TNF-α expression than GF mice (13,48). Moreover, microbiota might alter bone resorption through effects on B-cell production of osteoprotegerin (62), an inhibitor of osteoclast formation, as microbiota are known to affect B-cell development (63).…”
Section: Discussionmentioning
confidence: 99%
“…Crohn's disease can affect the GI tract anywhere from the mouth to the anus, with the most common area affected being the ileum. Ulcerative colitis however, is specific to the colon (154,155). In 2014 IBD was reported to affect 1.6 million Americans and as many as 70,000 new cases are reported per year (CCFA).…”
Section: Immune Involvement and Gut-bone Signaling In Pathophysiologymentioning
confidence: 99%
“…Because bone marrow is present within the bone structure, it is conceivable that intestinal inflammation such as what is seen in IBD can have profound influences not only on bone marrow composition but also on bone cells themselves and this is aided by changes in and influence of inflammatory cytokines. Previous studies in animal models of IBD demonstrate that inflammatory cytokines such as TNFα, IL-1α, IL-1β, IL-6, IL-11, and IL-17A are linked to decreased bone volume, bone formation rates, and osteoid surface (154,160164). In some studies, osteoclast surface is increased which further exacerbates bone loss (160).…”
Section: Immune Involvement and Gut-bone Signaling In Pathophysiologymentioning
confidence: 99%